Caracterización de la biodiversidad de insectos en pasto miel (Paspalum dilatatum) en la microcuenca del rio Yungañán cantón Pujilí 2018. - Maigua Bonilla, Vanessa Fernanda (2018)
The objective of this research was to analyze the abundance and richness of the crawling insects of eight collected transects on honey grass (Paspalum dilatatum), in Yungañán river microbasin. The data correspond to a serie of sampling in pitfall traps, starting at geographic point 715630 x; 9894808 y, at 2280.7 mosl. And ending at 707469 x; 9888713 y, at 640.4 mosl, giving 320 samples. Dynamic tables were used to determine alpha diversity and the EstimateS 9 program was used to get the Shannon-Wiener index, accumulation curves and standard deviation. In the place were found 10 orders that group 80 families with an abundance of 8011 insects. The transects of greater diversity according to the Shannon-Wiener index were two with 2.75, the fourth with 2.99 and the sixth with 3, in relation to the transects one with 2.49, three with 2.27 and eight with 2.19 that present low wealth to get greater anthropogenic activity. At the accumulation curves, a 90% acceptance of the sampling according to the standard deviation graphs is reached. The order with the greatest diversity is Coleoptera with 20 families, followed by the Diptera order with 15 families, hymenoptera with 12 families, the hemiptera order with 10 families and orthoptera with 5 families. The order of least diversity was siphonaptera with a family. Transect four is the most diverse and abundant with 43 families of insects, in relation to transects eight and three with 18 and 13 families respectively according to the expected wealth.